Engaging communities in managing multiple hazards: Reflections from small islands in North Sulawesi, Indonesia. Issue 2 (May 2016) - Rampengan, Mercy M.F.; Law, Lisa; Gaillard, J.C.; Boedhihartono, Agni Klintuni; Sayer, Jeffrey
Abstract : Participatory methods are a common approach for giving voice to local communities in hazard and disaster research. Drawing on a study that trialled and modified a range of participatory methods in North Sulawesi, eastern Indonesia, this paper reflects on how such methods help document the capacities of small island communities. We assessed capacity from a sustainable livelihoods perspective, identifying the assets that enable villagers to cope with hazards. This overall approach promoted a discourse of strengths and resourcefulness, contrasting with vulnerability and needs‐assessment approaches common to government and non‐governmental organizations, which tend to focus on weaknesses and can sometimes fuel undeliverable expectations of funding. We provide a critical reflection on participatory methods and their significance for researchers, policy makers and funding agencies working with communities in hazard‐prone regions.